Coevolution of the Ile1,016 and Cys1,534 Mutations in the Voltage Gated Sodium Channel Gene of Aedes aegypti in Mexico. - Farah Z Vera-Maloof; Karla Saavedra-Rodriguez; Armando E Elizondo-Quiroga; Saul Lozano-Fuentes; William C Black Iv (PLoS Neglected Tropical Diseases)
Background Worldwide the mosquito Aedes aegypti (L.) is the principal urban vector of dengue viruses. Currently 2.5 billion people are at risk for infection and reduction of Ae. aegypti populations is the most effective means to reduce the risk of transmission. Pyrethroids are used extensively for adult mosquito control, especially during dengue outbreaks. Pyrethroids promote activation and prolong the activation of the voltage gated sodium channel protein (VGSC) by interacting with two distinct pyrethroid receptor sites [1], formed by the interfaces of the transmembrane helix subunit 6 (S6) of domains II and III. Mutations of S6 in domains II and III synergize so that double mutants have higher pyrethroid resistance than mutants in either domain alone. Computer models predict an allosteric interaction between mutations in the two domains. In Ae. aegypti, a Ile1,016 mutation in the S6 of domain II was discovered in 2006 and found to be associated with pyrethroid resistance in field populations in Mexico. In 2010 a second mutation, Cys1,534 in the S6 of domain III was discovered and also found to be associated with pyrethroid resistance and correlated with the frequency of Ile1,016. Methodology/principal findings A linkage disequilibrium analysis was performed on Ile1,016 and Cys1,534 in Ae. aegypti collected in Mexico from 2000-2012 to test for statistical associations between S6 in domains II and III in natural populations. We estimated the frequency of the four dilocus haplotypes in 1,016 and 1,534: Val1,016/Phe1,534 (susceptible), Val1,016/Cys1,534, Ile1,016/Phe1,534, and Ile1,016/Cys1,534 (resistant). The susceptible Val1,016/Phe1,534 haplotype went from near fixation to extinction and the resistant Ile1,016/Cys1,534 haplotype increased in all collections from a frequency close to zero to frequencies ranging from 0.5-0.9. The Val1,016/Cys1,534 haplotype increased in all collections until 2008 after which it began to decline as Ile1,016/Cys1,534 increased. However, the Ile1,016/Phe1,534 haplotype was rarely detected; it reached a frequency of only 0.09 in one collection and subsequently declined. Conclusion/significance Pyrethroid resistance in the vgsc gene requires the sequential evolution of two mutations. The Ile1,016/Phe1,534 haplotype appears to have low fitness suggesting that Ile1,016 was unlikely to have evolved independently. Instead the Cys1,534 mutation evolved first but conferred only a low level of resistance. Ile1,016 in S6 of domain II then arose from the Val1,016/Cys1,534 haplotype and was rapidly selected because double mutants confer higher pyrethroid resistance. This pattern suggests that knowledge of the frequencies of mutations in both S6 in domains II and III are important to predict the potential of a population to evolve kdr. Susceptible populations with high Val1,016/Cys1,534 frequencies are at high risk for kdr evolution, whereas susceptible populations without either mutation are less likely to evolve high levels of kdr, at least over a 10 year period.